Search for a singly produced third-generation scalar leptoquark decaying to a tau lepton and a bottom quark in proton-proton collisions at root s=13 TeV - (:unkn) unknown (SPRINGER, 2018)
A search is presented for a singly produced third-generation scalar leptoquark decaying to a tau lepton and a bottom quark. Associated production of a leptoquark and a tau lepton is considered, leading to a final state with a bottom quark and two tau leptons. The search uses proton-proton collision data at a center-of-mass energy of 13 TeV recorded with the CMS detector, corresponding to an integrated luminosity of 35.9 fb(-1). Upper limits are set at 95% confidence level on the production cross section of the third-generation scalar leptoquarks as a function of their mass. From a comparison of the results with the theoretical predictions, a third-generation scalar leptoquark decaying to a tau lepton and a bottom quark, assuming unit Yukawa coupling (lambda), is excluded for masses below 740 GeV. Limits are also set on lambda of the hypothesized leptoquark as a function of its mass. Above lambda = 1.4, this result provides the best upper limit on the mass of a third-generation scalar leptoquark decaying to a tau lepton and a bottom quark.
Keywords: Beyond Standard Model; Hadron-Hadron scattering (experiments); CONSTRAINTS